[18F]AlF-NOTA-ADH-1: A new PET molecular radiotracer for imaging of N-cadherin-positive tumors - Liu, Zhenfeng; Wen, Guanghua; Huang, Yuqiao; Dong, Yanzhao; Wang, Zewei; Alhaskawi, Ahmad; Zhang, Shuyi; Wang, GuoLin; Ye, Qianni; Zhou, Haiying; Lu, Hui; Dong, Mengjie (Frontiers in Oncology, 2023)
Background The cell adhesion molecule (CAM) N-cadherin has become an important target for tumor therapy. The N-cadherin antagonist, ADH-1, exerts significant antitumor activity against N-cadherin-expressing cancers. Methods In this study, [18F]AlF-NOTA-ADH-1 was radiosynthesized. An in vitro cell binding test was performed, and the biodistribution and micro-PET imaging of the probe targeting N-cadherin were also studied in vivo. Results Radiolabeling of ADH-1 with [18F]AlF achieved a yield of up to 30% (not decay-corrected) with a radiochemical purity of >97%. The cell uptake study showed that Cy3-ADH-1 binds to SW480 cells but weakly binds to BXPC3 cells in the same concentration range. The biodistribution results demonstrated that [18F]AlF-NOTA-ADH-1 had a good tumor/muscle ratio (8.70±2.68) in patient-derived xenograft (PDX) tumor xenografts but a lower tumor/muscle ratio (1.91±0.69) in SW480 tumor xenografts and lowest tumor/muscle ratio (0.96±0.32) in BXPC3 tumor xenografts at 1 h post-injection (p.i.) These findings were in accordance with the immunohistochemistry results. The micro PET imaging results revealed good [18F]AlF-NOTA-ADH-1 tumor uptake in pancreatic cancer PDX xenografts with strong positive N-calcium expression, while lower tumor uptake in SW480 xenografts with positive expression of N-cadherin, and significantly lower tumor uptake in BXPC3 xenografts with low expression of N-cadherin, which was consistent with the biodistribution and immunohistochemistry results. The N-cadherin-specific binding of [18F]AlF-NOTA-ADH-1 was further verified by a blocking experiment involving coinjection of a non radiolabeled ADH-1 peptide, resulting in a significant reduction in tumor uptake in PDX xenografts and SW480 tumor. Conclusion [18F]AlF-NOTA-ADH-1 was successfully radiosynthesized, and Cy3-ADH-1 showed favorable N-cadherin-specific targeting ability by in vitro data. The biodistribution and microPET imaging of the probe further showed that [18F]AlF-NOTA-ADH-1 could discern different expressions of N-cadherin in tumors. Collectively, the findings demonstrated the potential of [18F]AlF-NOTA-ADH-1 as a PET imaging probe for non-invasive evaluation of the N-cadherin expression in tumors.